Research Interrupted: A Reflection on Digitizing Sarah Sophia Banks’s Collections and Access to Ephemeral Materials - Wills, Kacie L.; Hayes, Frica Y. (Romanticism on the Net, 2020)
In this reflection, we consider the interruptions to archival research caused by COVID-19 and share some of the challenges we have faced moving forward with our digital project on Sarah Sophia Banks’s ballooning scrapbook. We address some of the problems of archival access and explore potential solutions offered by digitized ephemeral materials. In light of recent scholarship that establishes ephemera as a Romantic-era technology that mediates our relationship to various forms of public knowledge, we highlight the scholarly opportunities made available by digital interfaces and tools.